Metamaterial Embedded Wearable Rectangular Microstrip Patch Antenna - J. G. Joshi; Shyam S. Pattnaik; S. Devi (International Journal of Antennas and Propagation)
This paper presents an indigenous low-cost metamaterial embedded wearable rectangular microstrip patch antenna using polyester substrate for IEEE 802.11a WLAN applications. The proposed antenna resonates at 5.10 GHz with a bandwidth and gain of 97 MHz and 4.92 dBi, respectively. The electrical size of this antenna is 0.254λ×0.5λ. The slots are cut in rectangular patch to reduce the bending effect. This leads to mismatch the impedance at WLAN frequency band; hence, a metamaterial square SRR is embedded inside the slot. A prototype antenna has been fabricated and tested, and the measured results are presented in this paper. The simulated and measured results of the proposed antenna are found to be in good agreement. The bending effect on the performance of this antenna is experimentally verified.